European Identity and University Students: A Comparative Study of Italy and Belgium - Jacobone, Vittoria; Giuseppe, Moro (Italian Sociological Review, 2016)
The present study aims to explore the experience of direct beneficiaries of the Erasmus programme in the perspective of the economic, cultural, political and social contexts in which the work was carried out. The research involved 287 Erasmus students, 146 Italian and 141 Belgian, enrolled at the University of Bari (Italy) and UCL Louvain-la-Neuve (Belgium) respectively. While the economic and political conditions of two Old Member States of the EU may bear similarities, the period of mobility brings to light a range of implications for students in the two countries. With respect to cultural and civic dimensions, the findings are of particular interest: living and studying abroad contributes, regardless of nationality, to the development of personal and intercultural skills. It would also appear to influence the development of a European identity, in this case closely linked to the local political landscape.